Interleukin-2 as a predictor of early postoperative atrial fibrillation after cardiopulmonary bypass graft (CABG). - Hak, Ł; Myśliwska, J; Wieckiewicz, J; Szyndler, K; Siebert, J; Rogowski, J (2009)
Recently, inflammation has been considered as a risk factor of postoperative atrial fibrillation (PAF). The main purpose of this study was to estimate the connections between occurrence of PAF and cytokine release. Thirty-three patients who qualified for cardiopulmonary bypass graft (CABG) were included in the study. Blood was taken from all of them before CABG, then 3 h, 24 h, and 72 h afterwards. Cytokine (IL-6, IL-2, IL-4, IL-10, IFN-gamma, TNF-alpha) concentration was measured at every time point. Eleven patients developed atrial fibrillation after the CABG. Five of them developed PAF until 1 day post-CABG and six of them after 1 day post-CABG. Patients who developed PAF before 1 day post-CABG were characterized by a higher level of IL-2 in sera before 24 h and 72 h post-CABG compared with patients without PAF. Moreover, the PAF before 1 day post-CABG group was also characterized by the higher level of IFN-gamma and IL-10 at 24 h after intervention. Analysis of patients who developed PAF after 1 day post-CABG revealed a higher level of IL-10 and IFN-gamma at 24 h post-CABG compared with patients without PAF. In this study, we have shown for the first time a straightforward connection between IL-2 sera levels and the development of PAF shortly after CABG.